The European Union, antisemitism, and the politics of denial - Elman, R. Amy 1961- (Studies in antisemitism, 2014)
"Copublished with the Vidal Sassoon International Center for the Study of Antisemitism, this study asks if the European Union (EU) has the capacity or the will to counter antisemitism. The desire to counter antisemitism was a significant impetus toward the formation of the EU in the twentieth century and now prejudice against Jews threatens to subvert that goal in the twenty-first. The European Union, Antisemitism, and the Politics of Denial offers an overview of the circumstances that obliged European political institutions to take action against antisemitism and considers the effectiveness of these interventions by considering two seemingly dissimilar EU states, Austria and Sweden. This examination of the European Union's strategy for countering antisemitism discloses escalating prejudice within the EU in the aftermath of 9/11. The author contends that Europe's political actors have responded to the challenge and provocation of antisemitism with only sporadic rhetoric and inconsistent commitment, a halfhearted strategy for countering antisemitism that exacerbates skepticism toward EU institutions and their commitments to equality and justice. This exposition of the insipid character of the EU's response simultaneously suggests alternatives that might mitigate the subtle and potentially devastating creep of antisemitism in Europe. This study offers a new approach insofar as scholarly considerations of the EU's attempts to combat racism rarely focus on antisemitism, while scholarship on antisemitism rarely considers the political context of the European Union. "--